Breeding System and Response of the Pollinator to Floral Larceny and Florivory Define the Reproductive Success in Aerides odorata - Adit, Arjun; Singh, Vineet Kumar; Koul, Monika; Tandon, Rajesh (Frontiers in Plant Science, 2022)
Consumption of pollination reward by felonious means in a plant species can influence the foraging behavior of its pollinator and eventually the reproductive success. So far, studies on this aspect are largely confined to interaction involving plant-pollinators and nectar robbers or thieves. However, a foraging guild in such interactions may also include floral herbivores or florivores. There is a paucity of information on the extent to which nectar larcenists may influence the foraging behavior of the pollinator and reproductive fitness of plants in the presence of a florivore. We investigated various forms of larceny in the natural populations of Aerides odorata, a pollinator-dependent and nectar-rewarding orchid. These populations differed in types of foraging guild, the extent of larceny (thieving/robbing), which can occur with or without florivory, and natural fruit-set pattern. The nectariferous spur of the flower serves as an organ of interest among the foraging insects. While florivory marked by excision of nectary dissuades the pollinator, nectar thieving and robbing significantly enhance visits of the pollinator and fruit-set. Experimental pollinations showed that the species is a preferential outbreeder and experiences inbreeding depression from selfing. Reproductive fitness of the orchid species varies significantly with the extent of floral larceny. Although nectar thieving or robbing is beneficial in this self-compatible species, the negative effects of florivory were stronger. Our findings suggest that net reproductive fitness in the affected plant species is determined by the overarching effect of its breeding system on the overall interacting framework of the foraging guild.